2018
DOI: 10.5539/jas.v10n6p49
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Effect of Vegetable Oils on the Mycelial Growth of Macrophomina phaseolina (Tassi.). Goid

Abstract: Macrophomina phaseolina (Tassi.). Goid is the etiological agent of one of the major diseases in cowpea bean crop, commonly known as gray rot stem. Due to the lack of registered phytosanitary products to control this disease, the search for alternative control methods is increasingly common. The objective of this study was to evaluate the effect of essential oils on mycelial growth of M. phaseolina. The oils tested were Mentha sp., Eucalyptus spp., Copaifera sp., and Lippia gracilis at concentrations of 0.4; 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…However, nigella and cactus oils were the least effect tested ones. These results are in harmony with Ugulino et al, 2018 who reported that using essential oils could inhibite the mycelial growth of Macrophomina phaseolina. Beg and Ahmed 2002, reported that Fusarium chlamydosporum and Macrophomina phaseolina were found to be highly sensitive to clove oil.…”
Section: I-laboratory Experiments: Effect Of Some Plant Water Extract...supporting
confidence: 90%
“…However, nigella and cactus oils were the least effect tested ones. These results are in harmony with Ugulino et al, 2018 who reported that using essential oils could inhibite the mycelial growth of Macrophomina phaseolina. Beg and Ahmed 2002, reported that Fusarium chlamydosporum and Macrophomina phaseolina were found to be highly sensitive to clove oil.…”
Section: I-laboratory Experiments: Effect Of Some Plant Water Extract...supporting
confidence: 90%
“…Moreover, some extracts were able to induce the activity of defense enzymes in soybean plants inoculated with M. phaseolina (Lorenzetti et al, 2018). Additionally, Lippia gracilis oil extract showed an important inhibitory effect on the mycelial growth of M. phaseolina, becoming a promising alternative as control method (Ugulino et al, 2018). Furthermore, exogenous application of the synthetic strigolactone (SL) GR24 suppressed M. phaseolina hyphal branching.…”
Section: Plant Metabolitesmentioning
confidence: 99%
“…For example, the total inhibition of F. verticillioides was achieved by França et al [39], Yamamoto-Ribeiro et al [40] and Bonfin et al [41] using the Palmarosa (Cymbopogon martinii), Ginger (Zingiber officinale) and Rosemary (Rosmarinus officinalis L.) essential oils at concentrations of 0.2%, 2.500 µg ml -1 (0.25%) and 150 µg ml -1 (0.015%), respectively. On control of M. phaseolina, Khaledi et al [42] and Ugulino et al [43] found maximum inhibition using Peppermint (Mentha piperita L.) and Alecrim-da-chapada (Lippia gracilis) at concentrations of 2.000 ppm (0.2%) and 0.4 to 1.0%, respectively.…”
Section: Inhibition Percentage Of Clove Essential Oil Against Tested mentioning
confidence: 99%